At what age do Mexicans suffer the most financial stress? - Osvaldo García Mata (Journal of Economics, Finance and Administrative Science, 2024)
Purpose - Needs change as people get older. Procuring resources to satisfy them can generate anguish and insecurities in consumers due to their financial situation. This study aims to analyze the relationship between age and financial stress among Mexican adults and estimate the age of their maximum financial stress. Design/methodology/approach This study is based on constructing a financial stress indicator using the confirmatory factor analysis and linear regression models with a quadratic term, employing data from the National Survey on Financial Inclusion 2021. Findings Results show that the relationship between age and financial stress follows a quadratic pattern, with a maximum level at age 56, which varies according to sex, marital status, number of dependents, education and regions. These findings interest financial product designers and policy developers who aim to improve consumers' well-being. Research limitations/implications Longitudinal studies and indicators, such as financial fragility, are needed to facilitate refining models over time. Originality/value There is no evidence of studies that have addressed the age of maximum financial stress in Latin America. Doing so is relevant because identifying the stages in life when adults are most vulnerable to financial stress helps assess its causes more precisely, thus mitigating its adverse effects.
Keywords: D14; D15; G51; I31; 330; Aging; Financial stress; Financial well-being; Mexico; Midlife; Region